جدید اور اسلامی اقتصادی نظام کے روحانی پہلوؤں کا تقابلی مطالعہ: A Comparative Study of Spiritual Aspects of Modern and Islamic Economic Systems - Muhammad Saif Ullah Khalid; Dr Mufti Muhammad Ahmad; Hafiz Masood Elahi (Al Manhal Research Journal, 2024)
Contemporary economics, such as capitalism, communism, and Islamic economic systems, do not only explain how to manage finances, but also affect the entire order of human life, priorities and life goals. In economic methods other than Islam, ethics, spirituality, and human self-improvement are often neglected. Problems like falls arise. While the Islamic economic system seeks to promote moral and spiritual aspects, which not only increase the welfare of the individual but also help in creating a balanced and fair economic system. Spirituality means following moral principles beyond the material aspects of life. This concept is found in various religions, in which man is encouraged to focus on moral, spiritual and social benefit rather than mere material gain. But the economic rules of these religions did not actually take place in the world. While the economic system of the world has been successfully organized for several hundred years through the economic rules of Islam. Provided protection while in a beleaguered economic system the acquisition of capital is the main purpose of life and any moral or spiritual perspective that prevents the growth of capital is considered futile and futile. This research article clarifies the metaphysical differences between Islamic and contemporary economic theories.